Tracing sexual contacts of HIV-infected individuals in a rural prefecture, Eastern China - Lin Haijiang; He Na; Ding Yingying; Qiu Danhong; Zhu Weiming; Liu Xing; Zhang Tiejun; Detels Roger (BMC, 2012)
Abstract Background Contact tracing is especially useful for identifying an infection with few cases in the population, such as HIV in China. Little such research is available in China. Methods Every newly diagnosed HIV case from 2008-2010 in Taizhou Prefecture, Zhejiang Province in China, was invited to participate as an "index case" in a contact tracing survey by providing contact information for up to eight sexual contacts who themselves were approached for voluntary HIV counseling and testing (VCT). Those who tested HIV-positive were then subjected to another contact tracing survey. This process was repeated until no more sexual contacts were reported or tested positive. Results A total of 463 HIV-infected individuals were newly identified during the study period, including 338 cases who were identified from routine surveillance programs and 125 cases who were identified from the present contact tracing survey. Among these 463 cases, 398 (86.0%) served as 'index cases' in the survey, including 290 (85.8%) out of the 338 cases identified from routine surveillance programs and 108 (86.4%) out of the 125 cases identified from the present survey. These 398 'index cases' reported a total of 1,403 contactable sexual contacts, of whom 320 (22.8%) received HIV testing and 125 (39.1%) tested positive for HIV. Willingness to receive HIV testing was high among spouses and long term heterosexual or homosexual partners but extremely low among casual and commercial sex partners of 'index cases'. Consistent condom use was rare for all participants. A total of 290 independent sexual network components were constructed, with high complexity. Conclusion Contact tracing is useful for identifying new HIV infections from spouses or long term sexual partners of HIV-infected individuals. The complicated sexual networks existing between and beyond HIV-infected persons provide opportunities for rapid spread of HIV in such areas.